More than comparing with majorities: the importance of alternative comparisons between children from different minority groups - Alexandre, J.; Monteiro, M. B.; Waldzus, S. (International Journal of Psychology and Psychological Therapy, 2007)
Using a social identity perspective as the guiding framework, this article examines how children of minorities use alternative comparisons to achieve positive distinctiveness of their minority group. We conducted a quasi-experimental study with 60 Portuguese children (Black, White and Gypsy) who were asked for their group preferences and attributions towards their own and other groups. Majority children showed in-group favoritism on both preference and attribution measures, but members of both minorities showed greater preference for majority members as well as for members of the in-group than for members of the other minority group. We concluded that, as predicted by social identity theory, one creative identity management strategy is that minorities emphasize their similarity with the high status majority while downgrading another minority.